2010
DOI: 10.2190/ec.42.1.e
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Web-Based and Paper-Based Administration of Questionnaire Research Instruments in Authentic Contexts-of-Use

Abstract: Questionnaire instruments are routinely translated to digital administration systems; however, few studies have compared the differential effects of these administrative methods, and fewer yet in authentic contexts-of-use. In this study, 326 university students were randomly assigned to one of two administration conditions, paper-based (PBA) or web-based (WBA), and given a set of questionnaires. Instructions were to complete the instruments in an environment of their choice, and data included reporting context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Affect is also related to users' willingness to participate and to data quality (Hardré, Crowson, & Xie, 2010). People often respond to computers as entities with social identities or as extensions of the people behind or within digital systems (Dodge, 2005;Moon, 2000;Nass, Fogg, & Moon, 1996).…”
Section: Differential Effects By Administration Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Affect is also related to users' willingness to participate and to data quality (Hardré, Crowson, & Xie, 2010). People often respond to computers as entities with social identities or as extensions of the people behind or within digital systems (Dodge, 2005;Moon, 2000;Nass, Fogg, & Moon, 1996).…”
Section: Differential Effects By Administration Methodsmentioning
confidence: 99%
“…Of those published studies conducted in uncontrolled environments, most have not included any characteristics of user-chosen contexts-of-administration. For both paper and digital instruments, the context may be a public or social space, and conditions may include interacting with other people and engaging in other concurrent activities (Hardré, Crowson, & Xie, 2010). Among the range of potentially influential factors that surround research administration, context factors outside of researcher control may have a direct impact on participants during instrument completion.…”
Section: Introductionmentioning
confidence: 99%
“…For the second through fifth semesters of Study 2, we converted the paper survey to an electronic version and posted it onto SurveyMonkey™. We chose this approach since the reported difference between paper-pencil and online responses is minimal (Hardre, Crowson, and Xie 2010;Hardre et al 2007). We also converted to help ensure privacy, increase convenience, and boost the number of participants.…”
Section: Data Collectionmentioning
confidence: 99%
“…Research on effects of survey modes (performed among older respondents, in other settings, and using other measures) comparing paper-based administration methods with online administrations methods has reported somewhat mixed findings (Carini et al, 2003). Hardré et al (2010) found that scores of respondents in a paper-based condition were slightly higher than the scores of those in a web-based condition, whereas the opposite was found in a study by Carini et al (2003). Carini et al (2003) has indicated that mode effects were generally small, and other studies (Hardré et al, 2007(Hardré et al, , 2010 found no effect of the administrative method on the reliability of the measures.…”
Section: Discussionmentioning
confidence: 71%